University sport and scholarship funding for student-athletes: possibilities and limitations to sports performance - Alex Caiçara de Albuquerque; Emanuele Vasconcelos da Costa; Junior Vagner Pereira da Silva (Colégio Brasileiro de Ciências do Esporte, 2023)
ABSTRACT The study investigated the policy of funding sports scholarships to student-athletes linked to the Federal University of Mato Grosso do Sul, Brazil. This is exploratory and documentary research, with an analysis of the opening and results edicts of the Athlete Scholarship Program (2010-2021). The institution has the Athlete Scholarship Program. Scholarships were paid R$400.00, with an annual duration of 9 and 7 months, with emphasis on individual sports, especially wrestling, athletics, and swimming. It is concluded that the university presents a policy that favors the sport of institutional representation, however, not the high performance, given the low value of the scholarship and the non-payment of it in the first quarter of all the years analyzed.